Influence of Conflict Management Styles on Organizational Commitment among the Bank Employees - A. Rajasekar,; C.Kathiravan,; S. Velmurgan,; P.Mahalakshmi,; E.Chandramouli,; V.Suresh, (International Journal of Psychosocial Rehabilitation, 2019)
The research tries to identify the influence of conflict management styles on organizational commitment among the bank employees. Data were collected from 50 bank employees and data analyzed through path analysis. It is discovered that the avoiding and compromising of conflict management styles influences organizational commitment among the bank employees. But, it is discovered that the dominating of conflict management styles not influences organizational commitment among the bank employees. Finally, it is also discovered that the organizational commitment influences organizational effectiveness among the bank employees in Cuddalore district. Hence, the author concluded that the bank managers must provide for employees and teams to maintain a creative conflict management styles in banks that is dynamic, constructive, and then for organizational commitment.